2021
DOI: 10.36253/phyto-13123
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological aspects of resistance in wheat to Puccinia triticina, induced by Pseudomonas protegens CHA0 and β-aminobutyric acid

Abstract: After perception of specific biotic or abiotic stimuli, such as root colonization by rhizobacteria or selected chemicals, plants can enhance their basal resistance against pathogens. Due to its likely sustainability, this induced resistance will be valuable for disease management in agriculture. This study examined resistance against wheat leaf rust (Puccinia triticina) induced by Pseudomonas protegens CHA0 (CHA0) and β-aminobutyric acid (BABA). Seed dressing with CHA0 reduced the number of sporulating pustule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The dosing stages also had a role in the disappearance of the bacteria . This agrees with what was indicated by [14], that the BABA act as an antibacterial by the ability of the amino acid to increase the resistance of animals and strengthen their immune system and thus reduce the proliferation of bacteria. The study done by Jasim et al, [ 11 ] , shown in their research that BABA has a beneficial impact on bacterial resistance against staphylococcus bacteria when exposed to acid.…”
Section: Results and Discussion Isolation And Diagnosis Of Staphyloco...supporting
confidence: 92%
“…The dosing stages also had a role in the disappearance of the bacteria . This agrees with what was indicated by [14], that the BABA act as an antibacterial by the ability of the amino acid to increase the resistance of animals and strengthen their immune system and thus reduce the proliferation of bacteria. The study done by Jasim et al, [ 11 ] , shown in their research that BABA has a beneficial impact on bacterial resistance against staphylococcus bacteria when exposed to acid.…”
Section: Results and Discussion Isolation And Diagnosis Of Staphyloco...supporting
confidence: 92%
“…Induced resistance against Puccinia triticina has also achieved by treating wheat (cv. Arina) with the bene cia bacterium Pseudomonas protegens CHA0 (by seed coating) and the compound β-aminobutyric acid (BABA) (soil drenching) (Bellameche et al 2021). BABA was tested at high concentrations (10-20 mM), and a dose-dependent reduction of pustule formation was observed with greatest protection at 20 mM.…”
Section: Discussionmentioning
confidence: 99%
“…While infection of the plant with Cmm did not significantly increase the H 2 O 2 level (0.125 μg g −1 FW) compared with the control seedlings (0.115 μg g −1 FW), this level was almost doubled during the PsT-04c and PsT-130 treatments with approximately 0.200 μg g −1 FW. Accumulation of H 2 O 2 was reported as the mechanism of induced systemic resistance, following treatment by Pseudomonas biocontrol agents (De Vleesschauwer and Hoefte, 2006;Bellameche et al, 2021). H 2 O 2 plays a central role in plant resistance to pathogens as it can activate several defense reactions including the strengthening of physical barriers and development of the hypersensitivity reaction.…”
Section: Discussionmentioning
confidence: 99%